Patients' preoperative awareness of anesthesia - Bujauskienė, Lina; Gedrimė, Lina (Slauga. Mokslas ir praktika, 2024)
Research methods: systematic literature analysis and qualitative research – semi-structured interview. The sample of the qualitative research is 16 respondents. The data was analyzed using the method of qualitative content analysis. Conclusions. 1. Patients know what anesthesia is and for what purpose it is performed, most patients follow the preoperative preparation recommendations. Before the operation, patients want to be informed and know about the course of the operation, anesthesia, pre-operative requirements, risks and threats of complications, the postoperative period, rehabilitation. Patients emphasize that communication with healthcare professionals (doctors and nurses) before surgery is very necessary for them. The information provided to some patients was insufficient, there was a lack of communication. Patients prefer an individual conversation and written or visual information about pre-operative preparation, anesthesia in a language they understand, without difficult medical terms. 2. Nursing roles emerged as important factors in patients' preoperative period. It has been established that the communication of health care professionals, including nurses, and the time devoted to patients in meeting their needs have a significant impact on patient awareness.
Keywords: anesthesia; awareness; preoperative awareness; nurse